Resistance of Broiler Meat through Exposure to Extremely Low Frequency Magnetic Fields of 700 µT and 900 µT Intensities and Safety Risks to Health - Sudarti Sudarti; Lutfiana Ditta Sari; Elok Permatasari; Tania Ardiani (Postgraduate, University of Mataram, 2023)
This study aims to examine